SUSTAINABLE LUXURY: HOW UZBEKISTAN’S BOUTIQUE HOTELS ARE REDEFINING HOSPITALITY (Scientific Journal of Actuarial Finance and Accounting, 2025)
This study examines the impact of sustainability initiatives on revenue growth in boutique hotels in Uzbekistan. Using an econometric model with 200 observations, key variables analyzed include sustainable practices score, guest satisfaction, eco-certifications, local material usage, and employment of local staff. Results show that guest satisfaction and eco-certifications significantly enhance revenue, while local material usage and employment of local staff have minimal or negative effects. Findings suggest that policy incentives and training programs can improve sustainability’s financial viability. This study provides empirical insights for hoteliers and policymakers to balance sustainability and profitability in boutique hospitality.